Perceptions of Weight Change Among Romantic Partners: Considering Body Image, Relationship Experiences, Gender, and Sexual Orientation - Markey, Charlotte H.; August, Kristin J.; Kelly, Kristin; Dunaev, Jamie Price (Frontiers in Global Women's Health, 2022)
Romantic relationship experiences have been found to be relevant to body image and weight in adulthood. In this study, we investigated predictors of heterosexual, lesbian, and gay romantic partner’s (N = 500, Mage = 29.3) perceptions of their own and their partner’s weight at the beginning of their relationship and 4.8 years later, on average. Perceived changes in participants’ own weight status was associated with greater body dissastisfaction and longer relationship length. Perceived changes in partner’s weight status was associated with their partner’s BMI, as well as relationship quality. We also found that gender was important in understanding some of these associations. Implications of weight perceptions for individuals’ and their partner’s health and well being and the critical role of relationship quality are discussed in the context of the health regulation model.